2001
DOI: 10.1063/1.1415497
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary elevation of the glass transition temperature of thin polymer films grafted to silicon oxide substrates

Abstract: We used local thermal analysis and ellipsometry to measure the glass transition temperatures (T g ) of supported thin films of poly͑4-hydroxystyrene͒ ͑PHS͒ and hydroxy terminated polystyrene ͑PS-OH͒. The films were spuncast from solution onto silicon oxide substrates and annealed under vacuum at elevated temperatures to graft the polymer to the substrate. Grafting was verified and characterized in terms of the thickness of and the advancing contact angle of water on the residual layer after solvent extraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
131
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 55 publications
(82 reference statements)
8
131
1
3
Order By: Relevance
“…Where the interaction is not favourable, for example when a non-polar polymer is coated on native SiO 2 on a silicon wafer, the polymer conformation tends to favour loops, with the concomitant increase in free-volume and subsequent decrease in apparent T g . [17][18][19][20][21][22][23][24] This phenomenon has been explored for thermomechanical data storage in polymer thin-films. 25 The final, and often most challenging, phase of the embossing cycle is the separation of stamp and substrate, since the two have been pressed together at elevated temperatures and forces in evacuated chambers to assure conformality.…”
Section: Hot Embossing Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Where the interaction is not favourable, for example when a non-polar polymer is coated on native SiO 2 on a silicon wafer, the polymer conformation tends to favour loops, with the concomitant increase in free-volume and subsequent decrease in apparent T g . [17][18][19][20][21][22][23][24] This phenomenon has been explored for thermomechanical data storage in polymer thin-films. 25 The final, and often most challenging, phase of the embossing cycle is the separation of stamp and substrate, since the two have been pressed together at elevated temperatures and forces in evacuated chambers to assure conformality.…”
Section: Hot Embossing Processmentioning
confidence: 99%
“…Contact angles were measured with the submerged-point technique, surface roughness (RMS) was determined for the silane SAM on a silicon substrate, and pull-off force was determined for a silane-decorated SPM tip at a Zeonor 750R (PCO) interface. temperature at a rate of 20 uC min 21 . The samples were heated at a rate of 20 uC min 21 and T g was calculated from the resulting data.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in cases of very strong interactions between the polymer and the sub-strate, increases in T g with decreasing film thickness have been reported. [5][6][7][8] In addition, large differences in behavior have been observed between thin films supported on a substrate and freely standing films. The supported films do not show a dependence on the molecular weight and show a nonlinear dependence of T g on the film thickness (h): 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 The observed depression was subsequently verified by Jonas et al 3 and Park and McKenna, 4 although other work found T g increasing in confined glass formers. [5][6][7][8] The T g depression in ultrathin polymer films is even more striking than that in materials confined to nanopores, [1][2][3][4][35][36][37] being as great as 75 K for unsupported polystyrene (PS) films. 9,10 Changes in T g are important from both practical and fundamental standpoints.…”
Section: Introductionmentioning
confidence: 99%